Determinants of immunization coverage among children aged between 12-23 months in Makueni County, Kenya - Wambua, Meshach M.; Nyaberi, Jackline M.; Muregi, Francis W. (International Journal Of Community Medicine And Public Health, 2023)
Background: Globally, diseases that can be prevented through immunization claim the lives of more than 3 million individuals in the population, 1.5 million of whom are typically children under the age of five. Furthermore, vaccine-preventable diseases are to blame for about 3.5 million with disability worldwide. Only 86% of children worldwide have had vaccinations, making millions of youngsters susceptible to diseases that can be treated or prevented by administering vaccines. Immunization is the only effective way to prevent or treat certain disorders. Methods: Descriptive cross-sectional design was used. Semi-structured questionnaires given by interviewers to mothers and other caretakers in particular households were used to gather the necessary data. Multi-stage sampling technique was employed to select the questionnaire respondents the study area, a sample size of 384 eligible participants was used to collect quantitative data. Results: The study’s findings showed that Makueni county had an 82% vaccination coverage rate. This was a sign that the county had fallen short of the goal set by the WHO. From the inferential statistics analysis, there were significant association between vaccine uptake and immunization in all the four objectives examined i.e., p≤0.05. Conclusions: The study established that immunization coverage is high for children 23 months and below in Makueni County, with socio-demographic characteristics being the most important factor. It is advised that additional efforts be made to increase the uptake of immunization services. Along with improving their knowledge of child immunization, prenatal clinics should focus on improving the mothers’ health-seeking behaviour.